Modulation of Inflammatory and Regenerative Pathways by Channa striata Extract in End-to-End Anastomotic Wound Repair: A Systematic Review - Faizurrahman Andi Kusuma; Sigit Adi Prasetyo; Endang Sri Lestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Intestinal anastomotic healing is a complex process, often complicated by inflammation and impaired regeneration, leading to leakage and stricture. Channa striata (snakehead fish) extract, traditionally used for wound healing, possesses bioactive compounds with potential anti-inflammatory and regenerative properties. This systematic review aimed to critically appraise the in vivo evidence for the effects of Channa striata extract on inflammatory and regenerative pathways in end-to-end anastomotic wound repair. Methods: A comprehensive search of PubMed/MEDLINE, Scopus, Web of Science, Embase, and Cochrane Library databases was conducted for studies published between 2013 and 2024. Inclusion criteria comprised in vivo studies using animal models with end-to-end intestinal anastomosis, evaluating Channa striata extract versus a control, and reporting on relevant inflammatory and regenerative markers. Data extraction and risk of bias assessment (using SYRCLE's tool) were performed. Results: Seven studies met the inclusion criteria. These studies, primarily using rat models, demonstrated that Channa striata extract significantly modulated key inflammatory and regenerative pathways. Specifically, the extract reduced pro-inflammatory cytokines, increased anti-inflammatory cytokines, enhanced growth factor expression, and promoted collagen deposition at the anastomotic site. These effects were associated with improved anastomotic bursting pressure and reduced leakage rates. Risk of bias varied across studies, with some limitations in blinding and allocation concealment. Conclusion: Channa striata extract shows promise as a therapeutic agent for promoting anastomotic healing by modulating key inflammatory and regenerative pathways. However, further high-quality, standardized studies are needed to confirm these findings, elucidate precise mechanisms, and optimize extract formulation and dosage before clinical translation.